(untitled) (Revista Paradigma, 2020)
This article aims at analyzing the institute of the Popular Initiative as a form of democratic and popular participation in the decision-making process of the Brazilian State, in the Democratic Rule of Law paradigm. It evaluates the historical process of commotion capable of originating the laws approved with popular participation and the process that each one faced until becoming law. It demonstrates the difficulties that the Popular Initiative faces as an instrument of social control of the constituted powers and as an exercise of popular sovereignty. It recognizes that it needs to be revised if it is to become an effective instrument for popular participation and democratic and citizenship concretization.